(untitled) (Al-Academy, 2015)
Film and literature exchanges it’s influences since the early beginning of the motion pictures appearance .it was a phenomenon in other genres such as theatre ,short stories and novels .the film used out of this interaction with literature the content , themes and subjects whish were more attached to the society. based on that , the film gains it’s successes and wide spread of influences on it’s audiences who became more familiar with the motion picture style.Astrok , the French film critic wrote about “Camera the pain “ and called it as the a way of writing in the future .he was talking about the future’s role of the film .It is the importance of the film in the creation and documenting the life and its various fields.Because of the unique role of the film and its mass influences so that it became a priority for the scientists and for those who involves in art and culture in the countries and groups it made its achievements secretly in order to control on the investments so that the governments interfere and play another role in the cinema industry in order to use the films magic influences and it’s ability to shape the mentality and influence the behaviors as a Dr.”Ali Shlash “said in his book “the film critic”.It was a kind of competitive relationship in order to marketing the ideas and thoughts for different goals .Georges sadole , the film historian books “the film history “ refers to this roles of the filmmakers, producers , actors , actress , and others who made the big films achievements and took its role in the life of the society .the film in general reflected the movement of the reality and use ideas to influence the film expressive ability which will be clear within the research where I will the beginning and the nature of the achievements , the ideas that used in the filmmaking that cause its ability to be more ability in expressions and arts